The Work-Family Spillover Effects of Customer Mistreatment for Service Employees: The Moderating Roles of Psychological Detachment and Leader–Member Exchange - Zhang, Ran; Wu, Yunqiao; Ferreira-Meyers, Karen (Frontiers in Psychology, 2019)
Past literature in the area of employee–customer interactions suggests that being mistreated by customers is deemed one of the most important work-related stressors for service employees. However, little is known about the effects of customer mistreatment on the family domain. In a representative sample of 221 front-line employees in the East China hairdressing industry using three separate surveys administered 1 month apart respectively, the current study explores the mediation effects of work-to-family conflict (WFC) and the moderation effects of psychological detachment (PD) and leader–member exchange (LMX) on the relationship between customer mistreatment and family satisfaction (FS). The research revealed that the employees confronted with intensive customer mistreatment tended to experience high levels of WFC, and WFC mediated the effects of customer mistreatment on FS. In addition, both PD and LMX attenuated customer mistreatment’s direct effects on WFC and indirect effects on FS (via WFC). This study contributes to the managerial psychology literature related to the customer mistreatment construct and a better understanding of how PD and LMX act as a work-family spillover effect moderator of customer mistreatment on individuals.